Asymmetric α‐Hydroxylation of a Lactone with Vinylogous Pyridone by Using a Guanidine–Urea Bifunctional Organocatalyst: Catalytic Enantioselective Synthesis of a Key Intermediate for (20S)‐Camptothecin Analogues. Issue 2 (28th November 2013) - Watanabe, Tatsuya; Odagi, Minami; Furukori, Kota; Nagasawa, Kazuo
Abstract We have developed a catalytic asymmetric synthesis of (S)‐4‐ethyl‐6, 6‐(ethylenedioxy)‐7, 8‐dihydro‐4‐hydroxy‐1H‐pyrano[3, 4‐f]indolizine‐3, 10(4H)dione (5 a), a synthetic intermediate for (20S)‐camptothecin analogues. A key step in this synthesis is an asymmetric α‐hydroxylation of a lactone with a vinylogous pyridone structure (8 a) by using a guanidine–urea bifunctional organocatalyst. The present oxidation was successfully applied to the synthesis of C20‐modified derivatives of (+)‐C20‐desethylbenzylcamptothecin (13).